2020
DOI: 10.3390/ijerph17093036
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial Disorders in Adolescence and Youth, According to Structural, Emotional, and Cognitive Transdiagnostic Variables: A Systematic Review

Abstract: Transdiagnostic causal variables have been identified that have allowed understanding the origin and maintenance of psychopathologies in parsimonious explanatory models of antisocial disorders. However, it is necessary to systematize the information published in the last decade. The aim of the study was to identify through a systematic review, the structural, emotional and cognitive transdiagnostic variables in antisocial disorders of adolescence and youth. Recommendations for systematic reviews and meta-extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In addition, differences are found in the arousal dimension in the evaluation of all images, indicating, that the custody group has greater activation than the non-custody and student groups, in the perception of pleasant and neutral images. This result indicates the impulsivity component associated with young people with antisocial behavior (Rockstroh and McTeague, 2019;Toro et al, 2020) which is consistent with a recent study finding an association between higher ratings of arousal to positive images and attention deficit hyperactivity disorder symptoms in youth (Truedsson et al, 2019). Furthermore, the results showed that custody sample were associated with lower ratings of arousal to unpleasant images, and concurrently in line with previous finding with CU in youth samples (Truedsson et al, 2019;Szabó et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, differences are found in the arousal dimension in the evaluation of all images, indicating, that the custody group has greater activation than the non-custody and student groups, in the perception of pleasant and neutral images. This result indicates the impulsivity component associated with young people with antisocial behavior (Rockstroh and McTeague, 2019;Toro et al, 2020) which is consistent with a recent study finding an association between higher ratings of arousal to positive images and attention deficit hyperactivity disorder symptoms in youth (Truedsson et al, 2019). Furthermore, the results showed that custody sample were associated with lower ratings of arousal to unpleasant images, and concurrently in line with previous finding with CU in youth samples (Truedsson et al, 2019;Szabó et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, neuroticism, low levels of agreeableness, and low levels of conscientiousness are correlated with a specific kind of social media use-that is, the kind that seeks to gain from social media the attention and social support people might lack in their offline lives (Seidman, 2013), so also possibly defensive trolling. Another known personality-related explanation of online deviance has to do with the difficulties some people experience in regulating their own emotions, and the ramifications of their anger (Toro et al, 2020). This negative affect is known to spiral, completely consume the person, and reduce the person's inhibitions, prompting an urge to engage in corrective action towards the culprit (the person perceived to have caused the anger; Agnew, 1995).…”
Section: Personality Structurementioning
confidence: 99%
“…Other theories related to deviance covered in the literature reviews are social learning theory, social control theory, differential association theory, life-course perspectives, social disorganization, strain theory, subcultural theory, social concern theory, routine activities theory or situational approaches, lifestyle exposure theory, arousal theory, criminology's situational approach, rational choice, delinquent problem-solving, deviance regulation theory, interactionist conception, neo-cognitive learning theory, genebased evolutionary theory, desistance theories, neutralization theory, frustration theory, etc. In the majority of the literature reviews, deviance was not studied as a single phenomenon, but as it related to other factors such as religiosity (Adamczyk et al, 2017), family influence (parental communication (Roisko et al, 2014), parental styles (Ruiz-Hernández et al, 2019), parental control, family processes, family history of substance use), peer-related factors (peer influence (Leung et al, 2014), peer network, peer association, motivations of dissent in social groups), individual factors (animal cruelty (Chan and Wong, 2019a,b;Longobardi and Badenes-Ribera, 2019), victimization and sexual victimization [(McGrath et al, 2011;Dennis et al, 2012;Engström, 2021), child maltreatment (Fitton et al, 2020), non-emotional callousness and impulsivity (Toro et al, 2020), motivational processes (Agnew, 1995)]. Concerning online deviance, most of the systematic reviews refer to a specific type of behavior, which is cyberbullying (Kowalski et al, 2014;Watts et al, 2017;Vale et al, 2018;Rosa et al, 2019;Zych et al, 2019).…”
Section: Types Of Deviancementioning
confidence: 99%